The value of immunotherapy in children with initial short-term frequent seizures - Zhao, Yongheng; Li, Jun; Gao, Liang; Yang, Xiaofan; Zhao, Haiqing; Li, Yumei; Su, Li; Zhao, Xiaoyu; Ding, Hao; Li, Baomin (Frontiers in Neurology, 2022)
This study aimed to discuss clinical characteristics, therapy, and antibody prevalence in epilepsy (APE) score for short-term, frequent epileptic seizures in children who are autoimmune-antibody negative and respond well to immunotherapy. The clinical characteristics, imaging manifestations, electrophysiology, and effective treatment plan of 9 children who met the above criteria were retrospectively analyzed in the Pediatric Neurology Department of Qilu Hospital at Shandong University from June 2019 to December 2021. All 9 patients (6 boys, 3 girls; aged 13 months−11 years and 5 months, median 3.5 years) had acute-onset seizures within 3 months. All had previous normal growth/development with no family history of disease. Seizure types were focal motor seizures (6), generalized tonic-clonic seizures (2), and generalized secondary-to-focal (1); occurred >10 times/day; and lasted <1 min/episode. Formal treatment with ≥2 types of antiseizure medicine (ASM) achieved an unsatisfactory effect. Cranial magnetic resonance imaging showed an abnormal result in 1 case. The APE score was ≥4 in 3 cases and <4 in 6 cases. All patients experienced symptomatic relief with immunotherapy; subsequently, 8 patients were free of recurrence and 1 had significantly reduced seizure frequency. Autoimmune antibody screening is recommended for children who were previously well and have acute-onset epilepsy; high frequency, short-duration seizures; no good response to 2 types of ASM; and other etiologic factors excluded, even with APE score <4. Even with negative autoimmune antibody results, the possibility of autoimmune epilepsy should be considered for urgent initiation of immunotherapy, which can achieve good results.